2021
DOI: 10.3390/toxics9060130
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Restricted Feeding Modifies the Temporal Expression of CYP1A1 and Attenuated Damage Induced by Benzo[a]pyrene in Rat Liver When Administered before CYP1A1 Acrophase

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that heterodimerizes with the AhR nuclear translocator (ARNT) to modulate CYP1A1 expression, a gene involved in the biotransformation of benzo[a]pyrene (BaP). The AhR pathway shows daily variations under the control of the circadian timing system. Daytime restricted feeding (DRF) entrains the expression of genes involved in the processing of nutrients and xenobiotics to food availability. Therefore, we evaluate if temporal AhR, ARNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A previous study reported linkage between CYP1A1 polymorphisms and the risk of developing HCC [ 16 ]. Being the most active enzyme in converting procarcinogens into active compounds, CYP1A1 promotes the formation of DNA adducts [ 17 , 18 ] and bioactivation of exogenous procarcinogens of HCC [ 19 ]. Another study demonstrated that GNMT exerted its antitumor activities on hepatocarcinogenesis partially through binding to the CYP1A1 promoter region and inhibiting CYP1A1 expression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported linkage between CYP1A1 polymorphisms and the risk of developing HCC [ 16 ]. Being the most active enzyme in converting procarcinogens into active compounds, CYP1A1 promotes the formation of DNA adducts [ 17 , 18 ] and bioactivation of exogenous procarcinogens of HCC [ 19 ]. Another study demonstrated that GNMT exerted its antitumor activities on hepatocarcinogenesis partially through binding to the CYP1A1 promoter region and inhibiting CYP1A1 expression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies indicate that CYP1A1 was involved in both metabolic activation and detoxification of B[a] P in a context-dependent manner, even more detoxification than bioactivation. The deletion of CYP450 in hepatocytes caused the substantial loss of all hepatic CYP function; thus, hepatic CYP enzymes appeared to be more important for detoxification of B[a]P in vivo ( Ávila-Rosales et al, 2021;Reed et al, 2019). Inducible CYP1A1 was absolutely required for detoxication of oral B[a]P in mice (Nebert et al, 2013) (Arlt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%